2015
DOI: 10.1371/journal.pone.0117328
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450-Dependent Metabolism of Caffeine in Drosophila melanogaster

Abstract: Caffeine (1, 3, 7-trimethylxanthine), an alkaloid produced by plants, has antioxidant and insecticide properties that can affect metabolism and cognition. In vertebrates, the metabolites derived from caffeine have been identified, and their functions have been characterized. However, the metabolites of caffeine in insects remain unknown. Thus, using radiolabelled caffeine, we have identified some of the primary caffeine metabolites produced in the body of Drosophila melanogaster males, including theobromine, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 58 publications
2
51
0
Order By: Relevance
“…The over‐expressed Cyp6a8 we found in 91‐R is not known to metabolize DDT or confer resistance to DDT when expressed at high levels . The common induction of Cyp6a2 , Cyp6a8 , and Cyp6w1 in response to chemical challenge, and Cyp6a8 and Cyp6w1 up‐regulation in response to caffeine exposure may suggest their involvement in general detoxification or stress response pathways. Notably, a number of previous studies reported that multiple P450 genes such as Cyp6g1 and Cyp12d1 were over‐expressed in DDT‐resistant D. melanogaster strains, suggesting that Cyp6g1 and Cyp12d1 are globally associated with DDT resistance .…”
Section: Discussionmentioning
confidence: 86%
“…The over‐expressed Cyp6a8 we found in 91‐R is not known to metabolize DDT or confer resistance to DDT when expressed at high levels . The common induction of Cyp6a2 , Cyp6a8 , and Cyp6w1 in response to chemical challenge, and Cyp6a8 and Cyp6w1 up‐regulation in response to caffeine exposure may suggest their involvement in general detoxification or stress response pathways. Notably, a number of previous studies reported that multiple P450 genes such as Cyp6g1 and Cyp12d1 were over‐expressed in DDT‐resistant D. melanogaster strains, suggesting that Cyp6g1 and Cyp12d1 are globally associated with DDT resistance .…”
Section: Discussionmentioning
confidence: 86%
“…Moreover the metabolites of caffeine (theophylline, theobromine, paraxanthine) are also highly bioactive compounds that are capable of causing further effects [44]. This is especially relevant regarding theophylline, which is known to have a higher degree of affinity to AdoR in comparison to caffeine and its other metabolites [32].…”
Section: Discussionmentioning
confidence: 99%
“…The initial N-demethylation reaction (loss of one -CH3 group) is common in mammalians and insects, which is believed to be mediated by cytochrome P450 enzyme systems (i.e. CYP1A2 isoenzyme) (Berthou et al, 1991;Berthou et al, 1992;Coelho et al, 2015;Kot and Daniel, 2008). The N-demethylation reaction of antidiabetic agent metformin was also observed in Typha latifolia (Cui and Schröder, 2016).…”
Section: Transformation Of Caffeine In Radish Enzyme Extractsmentioning
confidence: 99%